2010
DOI: 10.1002/ceat.201000256
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of MMA and VAc Miniemulsion Polymerizations Using Miglyol and Castor Oil as Hydrophobe and Liquid Core

Abstract: Miniemulsion polymerization reactions of methyl methacrylate (MMA) and vinyl acetate (VAc) for the synthesis of biocompatible polymeric nanoparticles were comparatively studied. 2,2'-Azo-bis(isobutyronitrile) was used as initiator, lecithin as surfactant, and Miglyol 812 or castor oil as costabilizers. Despite the propagation coefficient of VAc being ten times higher than that of MMA, the reaction rates of the VAc polymerizations were much lower. In VAc polymerizations a higher amount of low-molar-mass polymer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 24 publications
2
18
0
Order By: Relevance
“…It has to be mentioned that Crodamol and OA did not appear in the molecular weight distribution since their molar mass are below those of the standards used in the calibration curve. A similar behavior has been observed for the miniemulsion polymerization of MMA with castor oil or andiroba oils used as costabilizers.…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…It has to be mentioned that Crodamol and OA did not appear in the molecular weight distribution since their molar mass are below those of the standards used in the calibration curve. A similar behavior has been observed for the miniemulsion polymerization of MMA with castor oil or andiroba oils used as costabilizers.…”
Section: Resultssupporting
confidence: 78%
“…Due to the polymer lower interfacial energy with water when compared to the costabilizer, it will tend to partition preferentially to the water interface, forming particles with a polymer shell and a core composed of the costabilizer. In order to obtain nanocapsules for biomedical applications, different biocompatible oils could be employed as costabilizers, such as caprylic/capric triglyceride castor oil, jojoba and andiroba oils, linoleic acid, and oleic acid …”
Section: Introductionmentioning
confidence: 99%
“…As these radicals are mainly formed in the beginning of the reaction (considering the higher value of k p1 ), this retarding effect is more pronounced at the early stages of polymerization. A similar effect with a decrease in the initial polymerization rate was observed in the polymerization of vinyl acetate or methyl methacrylate in the presence of unsaturated triacylglycerol . In the polymerization of acrylates with alkyd resins reported in the literature, the authors observed a decrease in the polymerization rate that led to a limiting final conversion.…”
Section: Resultssupporting
confidence: 76%
“…Therefore, the use of biocompatible polymers and solvent-free, natural, and nonionic emulsifiers such as lecithin, in addition of costabilizers based in oils and fatty acids, is preferred for biomedical applications [9,[23][24][25][26].…”
Section: International Journal Of Polymer Sciencementioning
confidence: 99%
“…PMMA nanoparticles were produced by the miniemulsion polymerization technique and the formulations were defined according to previous studies conducted in the research group in the synthesis of biocompatible nanoparticles for drug delivery [23][24][25][26]. Formulations used in particles synthesis are presented in Table 1 for nanospheres (NS) and nanocapsules (NC).…”
Section: Pmma Nanoparticles Synthesis For Progesterone En-mentioning
confidence: 99%